The Transformation of Islamic Religious Education Teachers' Creativity through School Supervisor Mentoring - Kaso, Nurdin (State Islamic Institute of Palopo, 2025)
This research uses pedagogical, psychological, sociological, and normative theological approaches, postpositivism. This study will describe the performance of supervisors in increasing the creativity of Islamic religious education teachers. This research took place at SMPN 2 Bulukumba. Sources of data in the form of primary data come from supervisors, principals, PAI teachers, while secondary data is taken from documents related to research. The instrument used in data collection is the researcher himself, whose function is to determine and select informants as data sources, analyze data, interpret data; and instruments in data collection are observation, interviews, and documentation. Through collecting, processing, and analyzing data, the results of research on the performance of PAI supervisors at SMP Negeri 4 Masamba are illustrated. 1. The performance of PAI supervisors at SMP Negeri 4 Masamba has not been maximized; this is due to the lack of supervisors. 2. There are still supervisors who have multiple positions, so that impacts the lack of guidance for PAI teachers. 3. The creativity of PAI teachers at SMP Negeri 4 Masamba is good because the implementation of learning, both preparation and administration, implementation, and evaluation of learning outcomes can show an increase in creativity well. 4. Factors inhibiting supervisors' performance are the internal factors of supervisor recruitment, the presence of supervisors, and external factors of the affordability of the supervisory location. 5. Supervision on increasing the creativity of PAI teachers at SMP Negeri 4 Masamba is still very minimal.